The labour attitude towards personal protective equipment in high rise construction / Nur Azlina Hanafi - Hanafi, Nur Azlina (Faculty of Architecture, Planning and Surveying, 2013)
The labour attitudes are defines the quality of a workforce. Someone might have the best skills in an organisation, but with a poor attitude the quality of his work will be low. It's agreed that some people with the right attitude might not have the right mental capacity to cope with the skill requirements of jobs, but it's easier to build skills in someone with the right attitude. Department of Safety and Health (DOSH) has issued by statistic checking at construction site is 1260 warning notices had been issues,110 case discipline labour about wearing safety equipment in site, it is because attitudes problem of labour is very lowest nowadays especially among migrant workers. Based on some objective is to examine safety equipment, labour behaviour towards applying safety equipment needs at construction site, the labourer must used safety equipment like Personal Protective Equipment (PPE) that has been provided in construction site. The government has state that labourer are under a duty to ensure their own health and safety and, as a result, must make appropriate use of all PPE provided. It is to identify accident or hazard among labour in high rise construction. The attitude of some workers who do not practice safety can affect building construction in terms of productivity. If workers are not wearing safety equipment, indirect construction work has also suffered. This is research to identify safety standard requirement in high rise construction. labourer who do not follow the rules may be to give penalties by Occupational Safety and Health Act 1994(OSHA) and another several department has related. After that, this research also to provide recommendations on effectively to reducing hazards on site. To achieve the objective, there are some research method uses such as Questionnaire, Observation, Site Visit and Interview person who in charge of the case study. Lastly, in analysis and finding it proves that there are still have labourer do not wear safety equipment although it been prepared, it all based from using of above research method